KNOWLEDGE NEXUS TO DRIVE THE GROWTH OF THE UNIVERSITY – USM VC - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 18 January 2016 – The University Knowledge-Based Nexus (UkBN) would be one of the bases for Universiti Sains Malaysia (USM) to generate significant impacts in the socio-economic development of the country and the world, through various knowledge-based activities.